2012
DOI: 10.1139/a2012-009
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses of the effects of river flow on fish movement and activity

Abstract: Estimating the timing and magnitude of fish movements relative to environmental factors can provide insight into why fishes behave as they do. To make broad-level inferences about fish movement in lotic environments, we conducted random-effects meta-analyses on the effects of river flow magnitude on (i) non-migratory movements, (ii) upstream migratory movements, (iii) downstream migratory movements, and (iv) fine-scale activity. We found a significant positive effect of river discharge on non-migratory movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…We also observed that annual variation in movement rates through the ladder co-varied with spring-summer discharge and temperature, possibly acting in concert with the physiological status of migrants (Radinger & Wolter, 2014;Skov et al, 2010;Taylor & Cooke, 2012). Consistent with the positive relationship between discharge and mountain whitefish movement we observed, upriver movement of adult coho salmon through the Landsburg Dam fish ladder during their spawning migration was positively associated with river flow and with change in flow from the previous day in two of three study years (Anderson & Quinn, 2007).…”
Section: Does Upstream Movement Vary Seasonally?supporting
confidence: 82%
“…We also observed that annual variation in movement rates through the ladder co-varied with spring-summer discharge and temperature, possibly acting in concert with the physiological status of migrants (Radinger & Wolter, 2014;Skov et al, 2010;Taylor & Cooke, 2012). Consistent with the positive relationship between discharge and mountain whitefish movement we observed, upriver movement of adult coho salmon through the Landsburg Dam fish ladder during their spawning migration was positively associated with river flow and with change in flow from the previous day in two of three study years (Anderson & Quinn, 2007).…”
Section: Does Upstream Movement Vary Seasonally?supporting
confidence: 82%
“…These results indicate that flow is an important factor influencing the movement patterns of T. bostocki and suggest that environmental flows will be a useful tool to facilitate the natural movement of this species.The strong association between flow and fish movement found in this study is consistent with numerous other studies that have found positive associations between river discharge and the extent and frequency of fish movement (see meta-analysis byTaylor & Cooke, 2012), including studies of T. bostocki(Beatty et al, 2010). Our seasonal (weekly movement) and flow pulse (daily movement) studies found that T. bostocki generally performed larger downstream movements during higher flows and smaller upstream movements during lower flows.…”
supporting
confidence: 91%
“…Furthermore, only a few authors have investigated the role of personality in other important spatial ecology metrics including HR (Minderman et al 2010), movement (Fraser et al 2001;Chapman et al 2011;Brodersen et al 2012), and site fidelity (Brodersen et al 2012). Indeed, individual differences in movement behaviors are a typical feature of spatial ecology data sets, particularly in fishes (Conrad et al 2011;Taylor and Cooke 2012), which often feature "resident" and "mobile" contingent strategies (Skalski and Gilliam 2000;Fraser et al 2001;Morrissey and Ferguson 2011;Radinger and Wolter 2013). Research on this heterogeneity has tended to focus on internal factors, such as body size and ontogeny, and external environmental cues, such as habitat-suitability, temperature, and light (Lucas and Baras 2001).…”
Section: Introductionmentioning
confidence: 99%